2012
DOI: 10.1029/2011jf002177
|View full text |Cite
|
Sign up to set email alerts
|

Modeling large scale shoreline sand waves under oblique wave incidence

Abstract: [1] The hypothesis that the formation and dynamics of large scale shoreline sand waves can be explained by a feedback mechanism between waves and nearshore morphology under very oblique wave incidence is explored with a quasi 2D nonlinear morphodynamic model. Using constant wave conditions it is found that if the wave incidence angle at the depth of closure is larger than about 45 the rectilinear coastline becomes unstable and a shoreline sand wavefield develops from small random perturbations. Shoreline sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 38 publications
6
53
0
Order By: Relevance
“…On the location, large scale as well as shorter undulations (with a length of approximately 6 km) have been observed, see also van den Berg et al (2012). This might suggest that shorter undulations formed by less high waves forms one kind of undulations, while the larger waves are associated with the larger scale.…”
Section: Stability Analysismentioning
confidence: 91%
“…On the location, large scale as well as shorter undulations (with a length of approximately 6 km) have been observed, see also van den Berg et al (2012). This might suggest that shorter undulations formed by less high waves forms one kind of undulations, while the larger waves are associated with the larger scale.…”
Section: Stability Analysismentioning
confidence: 91%
“…All modeling studies [ Ashton et al , ; Falqués and Calvete , ; Ashton and Murray , ; van den Berg et al , ; Kaergaard and Fredsoe , ] with the exception of Idier et al [] have found the existence of a critical angle for HAWI, and, indeed, observations suggest that high‐angle wave climates correlate with sand waves existence [ Ashton et al , ; Ashton and Murray , ; Medellín et al , ; Idier and Falqués , ; Kaergaard and Fredsoe , ]. However, to our best knowledge, the value of the critical angle has only been tested in the spit of Long Point (Lake Erie, Canada) by Ashton and Murray [].…”
Section: Discussionmentioning
confidence: 99%
“…We choose a maximum value of A = 0.3 m 1/3 based on the Dean [] relationship between the fall velocity and A , which for coarse sand of 2 mm gives A = 0.25 m 1/3 . As a comparison, existing shoreline sand wave studies using a Dean profile [ Falqués and Calvete , ; Kaergaard and Fredsoe , , ; Uguccioni et al , ; van den Berg et al , ; Idier et al , ] considered A coefficients falling in the range 0.08–0.2 m 1/3 . For the maximum value of β s , a value of 0.2 would be justified according to the literature [e.g., Wright and Short , ].…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An outline of the model is given in this section omitting the details, which can be found in van den Berg et al (2012). A Cartesian frame with horizontal coordinates x and y and vertical coordinate z is used, where y runs along the initial mean shoreline orientation, x increases seaward and z increases upward.…”
Section: Modelmentioning
confidence: 99%